MODELING THE FUEL CONSUMPTION OF FORWARDERS BASED ON DIFFERENT LOG SIZES AND FORWARDING DISTANCES - Rukomojnikov, Konstantin; Tsarev, Evgenii; Sergeeva, Tatiana; Gilyazova, Tatiana; Shirnin, Yurij (Journal of Applied Engineering Science, 2022)
The aim of the proposed study was to show the fuel consumption of various log skidders and to create models for estimating the fuel consumption for different forwarders operating in cutting areas with different tree size characteristics. Production tests of the forwarders' operation at various cutting areas have been carried out. In experimental studies, forwarders from different countries were used. In particular, forwarders: Amkodor-2682 (Belarus), Komatsu 840 (Japan), TB-1M-16A (Russia). To implement the experiment and estimate the fuel consumption by forwarders, a volumetric method of replenishing the fuel tank at the end of the machine's working cycle was chosen. As a result of the performed experimental studies, the mathematical models for calculating the fuel consumption of forwarders on the dimensional characteristics of trees and the distances of log forwarding have been substantiated. They are necessary for estimating fuel consumption under different operating conditions of forwarders. The results were obtained with a confidence level of 0.95. The coefficients of determination for forwarders: Amkodor-2682, Komatsu 840, TB-1M-16, were 0.81, 0.80 and 0.84, respectively. This shows a high proportion of the influence of the dimensional characteristics of the object of labor on the fuel consumption of machines. The use of the developed mathematical relationships will facilitate the planning and calculation of the operating costs of the forwarding equipment.
Keywords: skidding, log, fuel consumption rate, logging, forwarder